Dynamic characteristics of filled natural rubber for earthquake energy applications / Tee Yun Lu - Tee, Yun Lu (2018)
Apart from food and clothing, a secure shelter is a necessity for a civilised society. Buildings and structures are proves that a country is moving toward modernisation. During the service, high-rise buildings and architectural structures are prone to dynamic external forces such as earthquake and wind. Along this line, innovative means of enhancing structural functionality and safety against natural hazards such as active, hybrid and passive energy dissipation system have been carried out in recent years. Passive energy dissipation system is the preferable energy dissipation device due to its good performance, economic and easy maintenance. In this thesis, an original passive energy dissipation device in the form of sliding rubber damper (SRD) is proposed. The device is developed by utilizing the special characteristics of rubber as damper and metal plates as supporting material. In order to produce a device that is economic and durable, study on the dynamic characteristics of material is required. For this purpose, shear and combined tension-torsion fatigue tests on carbon black filled natural rubber are conducted. Two carbon black contents are considered: 10 wt% and 25 wt%. The fatigue test results are presented in the form of Wöhler curves where the maximum principal stretch and the strain energy density are used as fatigue predictors in combination with the concept of strain amplification factor to account for carbon black content. The modal analysis is subsequently carried out in order to investigate the vibration characteristics of the device. More precisely, the latter involves impact hammer testing and shaker testing on a structure model. Results showed that fatigue life of natural rubber with 25 wt% carbon black is longer than 10 wt%. Moreover, rubber with 25 wt% carbon black showed a better damping performance.